2014
DOI: 10.1074/jbc.m113.520510
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis-derived Lysine Gingipain Enhances Osteoclast Differentiation Induced by Tumor Necrosis Factor-α and Interleukin-1β but Suppresses That by Interleukin-17A

Abstract: Background:We previously reported that Kgp, a lysine gingipain, degraded osteoprotegerin, an osteoclastogenesis inhibitory factor, to enhance lipopolysaccharide-induced osteoclastogenesis. Results: Kgp enhanced tumor necrosis factor-␣-and interleukin-1␤-induced osteoclastogenesis. Conclusion: Kgp degraded osteoprotegerin more efficiently than other cytokines, which might be related to enhancement of osteoclastogenesis by Kgp. Significance: Degradation of osteoprotegerin may be a crucial event in periodontal os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Various inflammatory factors, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6, are able to stimulate osteoclast differentiation from monocyte-macrophages (7,8). A number of previous studies have reported that infection stimulates the activation of osteoclast differentiation, as well as the molecular mechanisms that trigger it (9,10). However, bone/fracture healing is a proliferative physiological process and requires a lot of new osteoblasts to accelerate the synthesis and calcification of bone, as well as the increase of bone volume and density (11).…”
Section: Introductionmentioning
confidence: 99%
“…Various inflammatory factors, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6, are able to stimulate osteoclast differentiation from monocyte-macrophages (7,8). A number of previous studies have reported that infection stimulates the activation of osteoclast differentiation, as well as the molecular mechanisms that trigger it (9,10). However, bone/fracture healing is a proliferative physiological process and requires a lot of new osteoblasts to accelerate the synthesis and calcification of bone, as well as the increase of bone volume and density (11).…”
Section: Introductionmentioning
confidence: 99%
“…[49,50] However, in other studies, the association of HSV-1 with chronic periodontitis was not noted.…”
Section: The Role Of Herpesvirus In the Pathogenesis Of Odontogenic Amentioning
confidence: 88%
“…Induction of osteoclastogenesis due to cleavage of osteoprotegerin [30,49] C. rectus LPS: Stimulation of synthesis by gingival prostaglandin fibroblasts е2, il-1 and il-6 [32] Groel: Induces secretion by gingival cells il-6 and il-8 [38,45] T. denticola Chymotrypsin-like protease: Lysis of the components of the intercellular matrix (hyaluronic acid, chondroitin sulfate, fibronectin, laminin, fibrinogen) [16,17] A. actinomycetocomitans 1. Activation TLR-4 and myd88: Stimulation of differentiation of blood monocytes into osteoclasts [22] 2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several reports have indicated that gingipains are involved in alveolar bone loss [2][3][4][5]. Although the mechanisms by which gingipains cause bone resorption have not been elucidated in detail, we found that a secreted form of the lysine-specific gingipain (Kgp) promotes differentiation of osteoclasts, which facilitate bone resorption [6][7][8]. In this review, the role of gingipains in alveolar bone loss during periodontitis is discussed, including our recent findings that Kgp mediates proteolytic degradation of osteoprotegerin (OPG), a protein that inhibits osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 92%
“…We therefore investigated whether gingipains induced osteoclast differentiation in vitro using a co-culture system of mouse osteoblasts and bone marrow cells [6][7][8]. The cells were treated with Kgp and RgpB purified from culture supernatants of P. gingivalis.…”
Section: Kgp But Not Rgpb Enhances Osteoclast Differentiation In Vitromentioning
confidence: 99%